Economic-environmental analysis of solar-wind-biomass hybrid renewable energy system for hydrogen production: A case study in Vietnam - Nguyen, Huu Hieu; Bui, Van Ga; Le, Khac Binh; Nguyen, Van Trieu; Hoang, Anh Tuan (Center of Biomass & Renewable Energy (CBIORE), 2025)
Combining biomass with solar and wind energy to produce electricity and hydrogen, referred to as the Solar-Wind-Biomass Hybrid Renewable Energy System (SWB-HRES), provides optimal economic and environmental efficiency. This paper presents research findings from a case study of SWB-HRES implemented in Hoa Bac commune, Danang City, Vietnam, utilizing HOMER software for system modeling and optimization. The study aims to identify the optimal configuration for SWB-HRES with hydrogen production and assess its compatibility with grid-connected SWB-HRES without hydrogen production. A detailed analysis of greenhouse gas (GHG) emission reductions corresponding to different system configurations is also provided. The results indicate that the optimal SWB-HRES configuration for Hoa Bac includes a 15-kW solar panel, a 9-kW wind turbine, an 8.3 kW syngas generator, a 20-kW electrolyzer, a 24-kW converter, and a hydrogen storage tank with a capacity of 1 kg. This setup supports an annual electricity load of 7,300 kWh and produces 1,183 kilograms of hydrogen per year. For grid-connected HRES with hydrogen production, the solar-biomass system demonstrates superior economic and environmental efficiency compared to the wind-biomass configuration. The economic efficiency of SWB-HRES with hydrogen production matches that of SWB-HRES selling electricity to the grid when the hydrogen cost is 4.5/kg for discontinuous syngas generator operation and 5/kg for continuous operation. Furthermore, integrating biomass energy into HRES proves to be an effective strategy for GHG emission reduction. For the same electricity output of 62,863 kWh/year, the solar-wind HRES without hydrogen production achieves a GHG emission reduction of 33 tons of CO2-eq, while the solar-wind-biomass HRES with hydrogen production achieves a reduction of 217 tons of CO2-eq. Given that the performance of HRES depends on geographic location, equipment availability, and energy pricing, practical implementations should validate simulation results with experimental data collected on-site.